Prevalence and experience of fatigue in survivors of critical illness: a mixed‐methods systematic review - Bench, S; Stayt, L; Shah, A; Dhiman, P; Czuber‐Dochan, W (Wiley, 2021)
We conducted a mixed methods systematic review to investigate the prevalence, experience and management of fatigue in survivors of critical illness. We identified 76 studies investigating fatigue or vitality in adults discharged from an intensive care unit and split the extracted data into three datasets: vitality scores from the Short Form Health Survey‐36 (n = 54); other quantitative data (n = 19); and qualitative data (n = 9). We assessed methodological quality using critical appraisal skills programme tools. We adopted a segregated approach to mixed‐methods synthesis. In a final step, we attributed combined results to one of four qualitative themes: prevalence and severity; contributing factors; impacts on quality of life; and assessment and management. Prevalence of fatigue ranged from 13.8 to 80.9%. Short Form Health Survey‐36 vitality scores were commonly used as a marker of fatigue. Vitality scores reached a nadir approximately one month following ICU discharge (mean (SD) 56.44 (32.30); 95%CI 52.92–59.97). They improved over time but seldom reached reference population scores. Associated biological, disease‐related and psychological factors included age, poor pre‐morbid status, sleep and psychological disturbance. Qualitative data highlight the profound negative impact of fatigue on survivors’ quality of life. Survivors seldom had any information provided on the potential impact of fatigue. No fatigue assessment tools specific to critical illness or evidence‐based interventions were reported. Fatigue is highly prevalent in survivors of critical illness, and negatively impacts recovery. Further research on developing fatigue assessment tools specifically for critically ill patients and evaluating the impact of pharmacological and non‐pharmacology interventions is needed.